Effects of The Probability and Magnitude of Punishment on Illegal Behavior (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This study systematically replicated Experiment 1 of Carreiro (2017), testing the effects of extreme values of punishment magnitude and probability (loss of points); and the learning history of legal and illegal (corrupt) responses. In a virtual scenario, 96 university students chose between a legal alternative, which provided low magnitude reinforcers (points); and an illegal one, which produced high magnitude reinforcers, with the possibility of punishment. There were five phases (with different punishment values and with baseline) in 16 different orders, composing 16 groups. The results suggest the effectiveness of punishment in reducing illegal behavior. The analysis of the matching law showed a high correlation between the ratio of illegal responses and the ratio of reinforcements, bias, and especially matching and undermatching. The values and orders that the punitive stimulus was presented produced different effects on illegal behavior, such as lower proportion in phases of high magnitude and probability.
Keywords: corruption; illegal; punishment; risk; matching law